2015
DOI: 10.1007/s10597-015-9965-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Gender and Obesity Among Adults with Mental Illnesses in a Community Health Screening Study

Abstract: The prevalence of obesity and its associations with gender, clinical factors, and medical co-morbidities were examined among 457 adults attending public mental health programs in 4 U.S. states. BMI was measured directly and other information was gathered by interview. Over half (59 %, n = 270) were obese including 18 % (n = 83) who were morbidly obese. In hierarchical ordinary least squares regression analysis controlling for demographic, psychiatric, medical, smoking, and health insurance statuses, women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
13
1
Order By: Relevance
“…This study found no association between MetS and sex, contrary to findings from several studies that have found an increased risk for MetS in women compared with men [14, 38, 39]. Studies have found that women are more likely to be obese yet obesity is a major risk factor for MetS [40]. One study also found that women have increased susceptibility to metabolic side effects of antipsychotic medication [41].…”
Section: Discussioncontrasting
confidence: 87%
“…This study found no association between MetS and sex, contrary to findings from several studies that have found an increased risk for MetS in women compared with men [14, 38, 39]. Studies have found that women are more likely to be obese yet obesity is a major risk factor for MetS [40]. One study also found that women have increased susceptibility to metabolic side effects of antipsychotic medication [41].…”
Section: Discussioncontrasting
confidence: 87%
“…The associations between obesity and a wide range of comorbidities differ between genders, for example: Migraine[ 103 ], depression, eating disorders, anxiety and other mental disorders[ 104 , 105 ], sleep apnea[ 106 ], hypertension[ 107 , 108 ], atrial fibrillation[ 109 ], certain cancers etc . While most gender-specific differences in obesity-related comorbidities have been investigated and documented in adults, one cannot exclude the possibility that these, at least partially, reflect differences in health problems among obese children and adolescents.…”
Section: From Evidence For Gender Differences In Health Conditions Tomentioning
confidence: 99%
“…Therefore, it is important to understand the impact of concomitant SUD for this growing population. Previous research shows that obesity and its complications are more prevalent in those with SUD because of diet and lifestyle, adverse effects of psychotropic medications, and higher prevalence of poverty ( 28 ). The presence of NAFLD also has the potential to affect outcomes related to SUD through altered pharmacokinetics and drug clearance ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%